FAKTOR-FAKTOR PENYEBAB SISWA MEMPEROLEH NILAI DIBAWAH KKM PADA MATA PELAJARAN MATEMATIKA, SAINS, DAN IPS SDN 010 BANGKO SEMPURNA - Saam, Zulfan Saam Zulfaan; Yakub, Elni Yakub Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstractThis study aims to determine the factors that cause students get under KKM on the subjects of Mathematics, Science, and Social Studies of students, teachers, and parents, which is triggered by the formulation of the problem, namely whether the factors that cause students gain value under KKM on the subjects of Mathematics, Science, and Social Studies of students, teachers, and parents. The method used in this research is descriptive method. SDN 010 research sites in Bangko Perfect. The subjects were students of class III, IV, and V are received grades below KKM on the subjects of Mathematics, Science, and Social Studies are drawn with probability sampling techniques. Data and data collection tools in the form of a questionnaire about the factors that cause students get under KKM of students, teachers, and parents are made by the researchers themselves based on the lattice with alternative answers very often, often, sometimes, rarely and never. Data analysis technique using the formula percentage (Anas Sudijono, 2004: 170). Conclusion of the study of aspects of 50.58% of students score below KKM cause, among others, lack of motivation to learn (63.85%), less physical state support (46.15%), lack of maturation (46.15%), and lack of interest (46.15%) students. From the aspect of teachers at 44.61% below the value of the KKM causes include lack of mastery of teaching materials (56.73%), lack of control of media (55.13%), are not capable of properly managing class (40.38%), lack of mastery method (37.50%), and lack of teacher relationships with students (33.33%). Then the parents of aspects of 51.17% below the value causes KKM include how parents educate error (54.81%), lack of economic (52.56%), and lack of parental (46.15%). As a follow-up to the researcher recommends that students have positive motivation in learning, improve attitudes Should students in learning, not just wait if there is homework or if asked parents to learn, so teachers learn the material that will be presented and well equipped with a hang of media interest, and that parents are trying to educate their children properly so that the childs behavior directed towards goodness, have a strong sense of responsibility and discipline in learning. Keywords: causes of learning difficulties, Value under KKM